Análise da variação morfológica em Caipirasuchus paulistanus Iori & Carvalho, 2011 e Caipirasuchus montealtensis (Andrade & Bertini, 2008) (Crocodylomorpha: Sphagesauridae) - Dias, Willian Alexandre Ferreira (Universidade Federal de São Carlos, 2018)
Caipirasuchus is a genus of Notosuchia that lived during the late Cretaceous in Brazil and, until the present, only found in the Adamantina Formation, Bauru Basin. Within this genus there are the Caipirasuchus montealtensis and the Caipirasuchus paulistanus species, often referred to as taxon brothers due to their morphological proximity. The morphological similarity raises questions about the taxonomy of these species. The main difference between C. montealtensis and C. paulistanus comes from the existence of the pterygoid chamber in C. montealtensis, a chamber that presents intraspecific variation. The main goal of this study was to analyze the morphological variations in the choana region in order to observe whether these variations could mean sexual dimorphism or speciation. Computed tomography has been used to internally explore the choana region and to evaluate the possible communication between the pterygoid structures and the airways in both C. montealtensis and C. paulistanus. The results obtained support the morphological disparities between C. montealtensis and C. paulistanus. It was possible to identify morphological differences in the pterygoid chamber of the C. montealtensis specimens, a complex secondary chamber is present in the paratype and in the juvenile individual and completely absent in the holotype. A communication between the pterygoid chambers and the airways was found in the juvenile C. montealtensis, suggesting possible functions related to vocalization. The new observations expand the knowledge about C. montealtensis and C. paulistanus anatomy, as well as suggesting the possible occurrence of a new species of Caipirasuchus, from the characters found in the juvenile paratype and C. montealtensis. A stratigraphy is important for the taxonomic elucidation of the group and a broader sampling would assist in the taxonomy and understanding the function of the pterygoid chamber.
Analysis of the morphological variation in Caipirasuchus paulistanus Iori & Carvalho, 2011 and Caipirasuchus montealtensis (Andrade & Bertini, 2008) (Crocodylomorpha: Sphagesauridae)
Keywords: Cretáceo; Bacia Bauru; Formação Adamantina; Notosuchia; Tomografia computadorizada; Paleoecologia; Cretaceous; Bauru basin; Formation Adamantina; Computadorized tomography; Paleoecology; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA::PALEOZOOLOGIA